Structure-based virtual screening and biological evaluation of novel small-molecule BTK inhibitors. (1st January 2022) - Lin, Tony Eight; Sung, Li-Chin; Chao, Min-Wu; Li, Min; Zheng, Jia-Huei; Sung, Tzu-Ying; Hsieh, Jui-Hua; Yang, Chia-Ron; Lee, Hsueh-Yun; Cho, Er-Chieh; Hsu, Kai-Cheng
Abstract: Bruton tyrosine kinase (BTK) is linked to multiple signalling pathways that regulate cellular survival, activation, and proliferation. A covalent BTK inhibitor has shown favourable outcomes for treating B cell malignant leukaemia. However, covalent inhibitors require a high reactive warhead that may contribute to unexpected toxicity, poor selectivity, or reduced effectiveness in solid tumours. Herein, we report the identification of a novel noncovalent BTK inhibitor. The binding interactions (i.e. interactions from known BTK inhibitors) for the BTK binding site were identified and incorporated into a structure-based virtual screening (SBVS). Top-rank compounds were selected and testing revealed a BTK inhibitor with >50% inhibition at 10 µM concentration. Examining analogues revealed further BTK inhibitors. When tested across solid tumour cell lines, one inhibitor showed favourable inhibitory activity, suggesting its potential for targeting BTK malignant tumours. This inhibitor could serve as a basis for developing an effective BTK inhibitor targeting solid cancers.